Contexto sócio-espacial de escolas públicas da cidade de Araguatins/TO e implicações para os indicadores educacionais. - Ferreira, Eneila de Cassia Maia (Universidade Federal do Tocantins, 2023)
In this dissertation, we are interested in focusing on the socio-spatial context of some public schools in Araguatins, Tocantins State, seeking to think about the extent to which certain socio-spatial differentiations specific to this context may tend to certain socio- spatial inequalities, with educational indicators as a reflection observatory. We are not